Antecedents and Consequences of Electronic Word-of-Mouth Halodoc - Cornellia Aninda Kusuma Putri; Margaretha Pink Berlianto (CV. Inara, 2024)
This study was conducted to determine the effect of electronic word of mouth on facilitating conditions, perceived risk, perceived interactivity, perceived usefulness, confirmation of halodoc performance expectations and price mediated by intention to continued use and patient satisfaction with halodoc. Data collection was carried out using total sampling of Halodoc application users by distributing questionnaires containing 45 questions with a Likert Scale of 1 - 5, then the data was analyzed using the PLS-SEM method. The results of this study state that facilitating conditions, perceived interactivity and perceived usefulness have a positive influence on intention to continued use of Halodoc, as well as perceived usefulness, confirmation of Halodoc performance expectations and price have a positive influence on patient satisfaction with Halodoc. Perceived risk has a negative influence on intention to continued use of Halodoc. Intention to continued use of Halodoc and patient satisfaction with Halodoc can mediate electronic word of mouth, but perceived interactivity and perceived usefulness do not have a significant effect on Intention to Continued Use of Halodoc.